2009
DOI: 10.12702/1984-7033.v09n02a08
|View full text |Cite
|
Sign up to set email alerts
|

RAPD-based genetic relationships in different Bougainvillea cultivars

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
(11 reference statements)
1
15
0
1
Order By: Relevance
“…This analysis can be used to infer hybrids parentages (Srivastava et al 2009). The divergent of the hybrids from each other suggested that they have less relationship because of different parentage (Ali et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis can be used to infer hybrids parentages (Srivastava et al 2009). The divergent of the hybrids from each other suggested that they have less relationship because of different parentage (Ali et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Bougainvillea, till date, only a few studies were conducted to assess the genetic variation including, growth behavior studies (Gupta et al, 2006, correlation studies (Singh et al, 2010. Although the characterization work in Bougainvillea is more dealt with RAPD markers they were not much preferred as suitable marker systems for diversity and evolutionary studies due to their less reliability and lower reproducibility (Chatterjee et al, 2007, Hammad 2009, Srivastava et al, 2009. Reduction of duplications in Bougainvillea through the development of molecular markers profile which also serves as a potential tool in cultivar identification.…”
Section: Flower Morphologymentioning
confidence: 99%
“…Nowadays, in different Brazilian regions, the cultivation of cucurbits is performed prevailingly by small farmers, which use familiar labor. These family farmers are the major responsible for the maintenance of the local varieties, from which the pumpkin cultivation, an allogamous plant, is also dependent in other regions of the world, such as Africa (Gwanama et al 2001) and Spain (Ferriol et al 2003a, Srivastava et al 2009, Mendes Paula et al 2010). …”
Section: Introductionmentioning
confidence: 99%